Polarized macrophages promote gestational beta cell growth through extracellular signal‐regulated kinase 5 signalling. Issue 9 (25th May 2022) - Jiang, Yinan; Chen, Apeng; Kline, Diana; Liu, Qun; Ma, Jie; Wang, Yan; Zhang, Ting; Qian, Jieqi; Nelson, Laura; Prasadan, Krishna; Hu, Baoli; Gittes, George K.; et al.
Abstract: Aim: To show that depletion of pancreatic macrophages impairs gestational beta cell proliferation and leads to glucose intolerance. Materials and Methods: Genetic animal models were applied to study the effects of depletion of pancreatic macrophges on gestational beta‐cell proliferaiton and glucose response. The crosstalk between macrophages and beta‐cells was studied in vivo using beta‐cell‐specific extracellular‐signal‐regulated kinase 5 (ERK5) knockout and epidermal growth receptor (EGFR) knockout mice, and in vitro using a co‐culture system. Results: Beta cell‐derived placental growth factor (PlGF) recruited naïve macrophages and polarized them towards an M2‐like phenotype. These macrophages then secreted epidermal growth factor (EGF), which activated extracellular signal‐regulated kinase 5 (ERK5) signalling in beta cells to promote gestational beta cell proliferation. On the other hand, activation of ERK5 signalling in beta cells likely, in turn, enhanced the production and secretion of PlGF by beta cells. Conclusions: Our study shows a regulatory loop between macrophages and beta cells through PlGF/EGF/ERK5 signalling cascades to regulate gestational beta cell growth.